(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To summarize epidemiological, clinical and risk-behavior features among first-visit patients with syphilis at the STI clinic, National Hospital of Dermatology and Venereology, 2025-2026. Subjects and methods: A cross-sectional descriptive analysis was performed on 471 patients with confirmed syphilis and treatment indication. Demographic data, occupation, sexual behaviors, reasons for attendance, time from condomless sex to consultation, symptom duration, clinical signs and disease classification were extracted from the study records. Each variable was analyzed according to the number of valid observations. Results: The mean age of the study subjects was 29.8 ± 11.0 years. The 25-34-year group accounted for 39.7%, followed by the 18-24-year group with 30.5%. Male patients accounted for 59.4%. The most frequent occupation was workers (26.1%), followed by non-disclosure of occupation (16.6%) and office employees (14.9%). Condomless sex was reported in 96.2%. The median interval from condomless sexual exposure to consultation was 30.0 (7.0-60.0) days; (66.7%) patients presented within 30 days after exposure. Among 149 patients with recorded symptom duration, the median duration before consultation was 17.5 (7.0-30.0) days. Early syphilis accounted for 34.7%, while cases with undetermined duration accounted for 62.8%. Mucocutaneous lesions and chancre were recorded in 21% and 11.7%, respectively. Conclusions: Patients were mainly young adults, and condomless sex was highly frequent. The large proportion of cases with undetermined duration underlines the need for systematic recording of exposure history, symptom onset and previous treatment. Syphilis screening should be integrated with risk-behavior counseling, partner notification and testing for other sexually transmitted infections.